Reducing of total harmonic distortion using passive filter simulation to suppress harmonic currents with the case: General Hospital, Universitas Kristen Indonesia Jakarta. Issue 1 (October 2021) - Elfando, D; Silalahi, E M; Stepanus, S; Widodo, B; Purba, R
Abstract: With the increasing need for and use of electrical energy amid increasingly rapid technological advances, especially in the use of electronic equipment in hospitals, it is necessary to pay attention to the problem of harmonics due to the use of non-linear electrical equipment. Therefore, it is necessary to measure the current and voltage THD for each non-linear equipment user. If the current and voltage THD values do not meet the standards, then a filter design is carried out so that the THD values meet the standards. Based on the results of THD measurements on the Main Distribution Panel (MDP) of RSU UKI, it was found that the THD of the voltage varied between 0.7877% - 2.4363% and the current THD varied between 5.3073% - 9.2363%. The measured THD value refers to the IEEE 519-2014 standard. If the THD value of the measurement results exceeds the IEEE 519-2014 standard, a harmonic filter is needed. With the simulated single tuned filter design, the current THD decreases within the standard value. The THD value of the current after installing the filter at the three MDP's of the RSU UKI, namely MDP A of 1.72%, MDP B of 0.64% and MDP C of 1.30%.